(untitled) (Revista Contexto & Educação, 2026)
The teaching of Science plays an important role in the development of Scientific Literacy, being able to promote, from the early years of schooling, not only the acquisition of new knowledge but also the development of citizens with investigative thinking, awakening curiosity. This process goes beyond the simple reproduction of scientific concepts, preparing the individual to act critically in a scientific and technological society. Therefore, this work aims to investigate the perceptions and experiences of three teachers of the Early Years of Elementary Education in public schools in the municipality of Pelotas/RS regarding the teaching of Science and their understandings about the aspects necessary for the effective implementation of scientific concepts in pedagogical practice. The research presents a qualitative approach and for data collection, a semi-structured interview was used. The results were analyzed through Content Analysis, a process in which three a priori categories emerged. For this work, one of the analysis categories called ’Science Teaching in the Early Years’ and its respective subcategories will be presented and analyzed. The results indicated that, despite the difficulties experienced by the teachers, all recognize the importance of Science teaching in stimulating curiosity and critical thinking. The teachers also reported using different teaching strategies to work on Science. One of the teachers, in addition to having a degree in Pedagogy, also has a degree in Biological Sciences, a fact that may influence her preference for experimental activities, while the other teachers indicated diversifying their practices more through the use of a greater number of teaching resources.